Pengaruh Kualitas Produk, Persepsi Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Es Coklat Ngetop di Surakarta - Mukhammad Akmal Filardi; Yuliar Kartika Wijayanti (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to determine the influence of Product Quality, Price Perception, and Service Quality on Customer Satisfaction of Popular Chocolate Ice in Surakarta. The population in this research are Ngetop Ice Chocolate consumers who are in Surabaya and have purchased the product more than once. This research also aims to analyze the influence of product quality, price perception, and service quality on customer satisfaction for Es Coklat Ngetop in Surakarta. Product quality is measured based on the taste, appearance and consistency of the chocolate ice served. Price perception is understood as a customer's view of the value of a product compared to the price they pay. Service quality is assessed from the responsiveness, competence and reliability of the service provided by the seller. The type of data used in this research is quantitative data. The sampling technique in this research used accidental with a sample of 100 respondents. The data collection technique uses a questionnaire method and data analysis in this research uses the t test and f test methods. In this research, the results show that product quality, price perception and service quality partially have a positive and significant effect on customer satisfaction. Simultaneously, these three independent variables have a positive and significant effect on customer satisfaction Based on the results of the SPSS version 29 F test, all independent variables simultaneously influence customer satisfaction. based on the results of the t test, it shows that the product quality variable has a positive and significant effect on customer satisfaction, the price perception variable has a positive and significant effect on customer satisfaction, and the service quality variable has a positive and significant effect on customer satisfaction